Optimizing Vancomycin dosing in a sample of critically ill patients comparing current practices to individualized dose regimen: A Randomized study. - Al-Khayyat, Noor Sameer; Ghareeb, Mowafaq Mohammed; Al-Moosawi, AbdulRasool Noori (Pharmacy Practice (1886-3655))
Background:In 2020, a revised consensus guideline of therapeutic monitoring of vancomycin for serious methicillin-resistant Staphylococcus aureus infections was published, and reviewed by many regulatory authorities Stated that, in patients with suspected or definitive serious MRSA infections, an individualized dose targeting area under the curve over 24 hour (AUC24) to minimum inhibitory concentration (MIC) ratio of 400 to 600 mcg*hr/mL should be advocated to achieve clinical efficacy and improving patient safety, while many hospitals in Iraq utilize fixed manufacturer-recommended dose for vancomycin in patients with normal renal function which is 30 mg/kg/d given as two or four divided daily doses. Objective: Comparing vancomycin AUC24/MIC ratio of patients receiving conventional vancomycin doses to patients receiving individualized doses calculated by pharmacokinetic dosing methods. Methods: A prospective randomized study conducted in the Intensive Care Units (ICU) of two tertiary centers at Baghdad Medical Complex (Baghdad Teaching Hospital and Ghazi Al-Hariri Hospital for Surgical Specialties), Patients were assigned alternately, 30 patients who met inclusion criteria were assigned to the conventional group (group 1), receiving the conventional dose of 1 g of vancomycin every 12 hours or any other dose prescribed by ICU physicians, representing the current practice; and 30 patients were assigned to the interventional group (group 2), where vancomycin dose was calculated by pharmacokinetic dosing method. Results: The target AUC24/MIC Ratio of 400 -- 600 mcg*hr/mL was achieved in 6 (20%) patients of group 1, and 16 (53.33%) patients of group 2, which was statistically significant with P-value 0.000. Conclusions: Individualized vancomycin dosing improved achievement of the therapeutic AUC24/MIC target versus conventional dosing (53.3% vs 20.0%) but was associated with increased nephrotoxicity.